Structural Support and Dynamics at the Tip - Christophel, J. Jared; Park, Stephen S. (Facial Plastic Surgery, 2012)
Controlled surgical alteration of the nasal tip remains one of the most difficult aspects of rhinoplasty. The appearance of the nasal tip depends on the underlying anatomy, and the long-term resultant anatomy depends on the structural dynamics and healing process. Many methods have been devised for altering the nasal tip and all do so via their ultimate effect on nasal tip structure and dynamics. This article summarizes the history of nasal tip structural and dynamic theories, reviews the fundamental effects of standard maneuvers on tip position and form, and finally discusses state of the art theories that synthesize classical thought and modern aesthetic goals.
Keywords: nasal tip support; nasal tip dynamics